Status assessment of the rare aquatic plant Groenlandia densa (L.) Fourr. (Potamogetonaceae) in the Western Balkans. Issue 2 (3rd April 2019) - Šegota, Vedran; Zlatković, Bojan; Vukov, Dragana; Alegro, Antun; Koletić, Nikola; Vuković, Nina; Rimac, Anja
ABSTRACT: Groenlandia densa is globally a widely distributed species; it has been recorded in the majority of the countries of the Western Balkans. However, the knowledge on its extant distribution in this particular area is limited and even controversial. In order to address this issue by tracking changes in species distribution over time and elucidating its current status in this area, we carried out a comprehensive survey of available literature sources and herbarium data, and performed field surveys. In Bosnia & Herzegovina, Montenegro and Croatia the species is most probably regionally extinct, while in Albania, Macedonia, Slovenia and Serbia G. densa occurs with only sparse records. Therefore, the most recent overview confirms this species as exceptionally rare in the Western Balkans. In Northern Europe the populations are declining due to various factors such as changes in climate and hydrology, prolonged periods of drought and irregular flooding, inappropriate water management, urbanization, eutrophication, etc., and in the Western Balkans we have observed the same general trend. As a threatened species, G. densa urges for active conservation measures and thus our recommendation would be to reassess this species at the European level.